Usefulness of Low-Dose Splenic Irradiation prior to Reduced-Intensity Conditioning Regimen for Hematopoietic Stem Cell Transplantation in Elderly Patients with Myelofibrosis - Etsuko Matsubara; Jun Yamanouchi; Riko Kitazawa; Taichi Azuma; Hiroshi Fujiwara; Takaaki Hato; Masaki Yasukawa (Case Reports in Hematology)
The Janus kinase (JAK) 1 and 2 inhibitor, ruxolitinib, was recently approved in Japan and has been effective in many patients with myelofibrosis (MF). Although the inhibitor decreases splenomegaly and relieves MF-related symptoms, allogeneic hematopoietic cell transplantation (HCT) remains as the only curative therapy for MF. The presence of splenomegaly has been reported as a risk factor for graft failure, delayed engraftment, and poor survival. Here, we report two elderly MF patients with massive splenomegaly and a JAK2 V617F mutation. These patients underwent splenic irradiation to decrease splenomegaly prior to HCT with a reduced-intensity conditioning (RIC) regimen. Massive splenomegaly gradually decreased by 4 Gy splenic irradiation. The subsequent RIC regimen involved 4 Gy total body irradiation and fludarabine and intravenous busulfan. In both patients, engraftment failure did not occur, and complete remission was achieved. The splenomegaly decreased, and MF-related symptoms were resolved. Furthermore, the JAK2 V617F mutation disappeared, and fibrosis in the bone marrow regressed. We suggest that splenic irradiation prior to the RIC regimen for HCT in elderly MF patients with massive splenomegaly is safe. Furthermore, the HCT protocols with splenic irradiation should be considered for patients who have not shown clinical benefits to optimal medical management such as treatment with ruxolitinib.